The economic contribution of rural grocery stores in Kansas - Miller, Hannah (Kansas State University, 2015)
The purpose of this study was to examine the economic contribution of rural grocery stores to the communities they serve. In addition, this study looked at the community characteristics that influence the level of economic contribution of a rural grocery store. The analysis was conducted for 163 Kansas rural grocery stores that were selected from cities with populations of fewer than 2,500 people. Regarding the first objective, household income changes and loss of business activity associated with each grocery store were estimated using the IMPLAN economic modeling system. To do so, changes in employment at each grocery store and household income in the community were measured assuming the loss of income that affected households in a city would face if they had to travel a greater distance to buy groceries. The economic contribution of rural grocery stores in Kansas averaged $644,413, ranging from $38,441 and $3,921,027. The results showed that population and location within the state had direct effects on the economic impact of a grocery store. With more complex economies in the eastern and south central parts of Kansas, these stores had a greater economic contribution than stores in the Southwest and Northwest. Communities in the western parts of Kansas would be the worst off from losing their grocery store because of increased travel costs they would incur by traveling the next alternative store. For the second objective, city and county characteristics that were thought to influence the level of the economic contribution of a store were tested. Two regression models were considered specifying the natural log of the economic contribution of the grocery store and the percentage of total value added the grocery store contributed to the county economy as the respective dependent variables. It was observed that population was one of the biggest drivers of the economic contribution of a grocery store. Other variables that were statistically significant in both models were the number of city households that had children, relative remoteness of the county, the number of convenience stores per 1,000 people, and the county wealth. In conclusion, this study showed that grocery stores have a significant impact on the communities that they serve. Both employment and travel costs had direct implications on the economic impact of a store. Additionally, demographic factors and other community characteristics influenced the level of impact that these grocery stores can have on their communities.
Keywords: rural; grocery stores; rural development; rural grocery stores; rural economic development; IMPLAN; Economics, Agricultural (0503)